Extremism and common mental illness: cross-sectional community survey of White British and Pakistani men and women living in England. (October 2020) - Bhui, Kamaldeep; Otis, Michaela; Silva, Maria Joao; Halvorsrud, Kristoffer; Freestone, Mark; Jones, Edgar
Abstract : Background: Mental illnesses may explain vulnerability to develop extremist beliefs that can lead to violent protest and terrorism. Yet there is little evidence. Aims: To investigate the relationship between mental illnesses and extremist beliefs. Method: Population survey of 618 White British and Pakistani people in England. Extremism was assessed by an established measure of sympathies for violent protest and terrorism (SVPT). Respondents with any positive scores (showing sympathies) were compared with those with all negative scores. We calculated associations between extremist sympathies and ICD-10 diagnoses of depression and dysthymia, and symptoms of anxiety, personality difficulties, autism and post-traumatic stress. Also considered were demographics, life events, social assets, political engagement and criminal convictions. Results: SVPT were more common in those with major depression with dysthymia (risk ratio 4.07, 95% CI 1.37–12.05, P = 0.01), symptoms of anxiety (risk ratio 1.09, 95% CI 1.03–1.15, P = 0.002) or post-traumatic stress (risk ratio 1.03, 95% CI 1.01–1.05, P = 0.003). At greater risk of SVPT were: young adults (<21 versus ≥21: risk ratio 3.05, 95% CI 1.31–7.06, P = 0.01), White British people (versus Pakistani people: risk ratio 2.24, 95% CI 1.25–4.02, P = 0.007) and those with criminal convictions (risk ratio 2.23, 95% CI 1.01–4.95, P = 0.048). No associations were found with life events, social assets and political engagement. Conclusion: Depression, dysthymia and symptoms of anxiety and post-traumatic stress are associated with extremist sympathies.